THE PROBLEM OF OSTEOPOROSIS IN PATIENTS WITH RHEUMATOID ARTHRITIS - Irina Mikhailovna Marusenko; O Yu Barysheva; N N Vezikova (Современная ревматология)
Objective. To estimate the frequency and degree of osteopenia and osteoporosis (OP) in patients with rheumatoid arthritis (RA) versus those in patients with osteoarthrosis (OA). Subjects and methods. The study included 150 patients aged above 18 years with the valid diagnosis of RA or OA, in whom the risk factors of OP were assessed. Bone mineral density (BMD) (the relative units were T test) of the lumbar spine in the frontal projection (LII-LIV) and the proximal femur (head, neck, WardXs region, and greater trochanter) were determined in all the patients by dichromatic X-ray absorption on a LUNAR DPX-NT densitometer. Results. A high frequency of osteopenia and OP predominantly due to BMD loss in the WardXs region and lumbar spine was observed in post-menopausal patients with RA. In postmenopausal patients with OP, osteopenia was commonly detectable at the level of the hip or vertebral column and OP was more characteristic for the lumbar portion. Regression analysis showed that among the postmenopausal patients with RA, women over 60 years of age, with low body mass index in the greater trochanter, and high disease activity in the femoral neck were at the highest risk for OP in the femoral neck and lumbar spine. Conclusion. The risk of osteopenia and OP is higher in RA than that in OA, low body mass index, old age, high disease activity, and a more severe disabling functional class RA being the most important risk factors